PENGUATAN BUDAYA LOKAL: IMPLEMENTASI EXTRAKULIKULER MELALUI SENI TARI DI SMP PGRI 2 SINGOSARI MALANG - Putri Mudianingrum, Tasya; Romadhon, Romadhon; Iswahyudi, Didik (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
Culture that grows and develops in one ethnic groups can be called local cultures. Cultural education locally, one of them can be implemented in activities extracurricular dance at school. But in reality Judging from the development of today's technological era draws students' attention from regional culture alone. Students are more likely to be enthusiastic practicing modern dance rather than traditional dance. Therefore, the concept in extracurricular dance learning requires other methods and approaches, so that students can have an interest and good response to the learning in question. This research aims to determine the implementation and strategies for strengthening local culture through dance at SMP PGRI 2 Singosari. This research uses qualitative with an interactive approach. Data collection techniques use observation, interviews and documentation. The results of the research show that the implementation of strengthening local culture through extracurricular dance at SMP PGRI 2 Singosari is strengthened by the policy of implementing extracurricular activities which are included in the school curriculum. Meanwhile, the strategy of strengthening local culture through extracurricular activities is realized by providing material related to dance, training in learning dance, showing videos such as dance, regional arts in PPKn learning, holding bull art performances and exhibitions filled with dance. In this way, strengthening local culture through dance has an impact on strengthening character